2017
DOI: 10.18632/oncotarget.15759
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group and ovarian reserve: a meta-analysis and systematic review

Abstract: Ovarian reserve reflects a woman's fertility potential. The ABO blood group system is a very stable genetic marker. Although many recent studies have explored the relationship between ABO blood group and ovarian reserve, a consensus has not yet been reached. This paper is the first meta-analysis and systematic review of the relationship between ABO blood type and ovarian reserve. We analyzed seven cross-sectional studies evaluating follicle stimulating hormone (FSH) or anti-Mullerian hormone (AMH) levels in 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A study by Nejat et al in 2011 reported that blood types A and AB are more associated with low ovarian reserve [57]. However, such results were not repeated in other subsequent studies, including a metaanalysis on the subject [58][59][60].…”
Section: Abo Blood Typementioning
confidence: 99%
“…A study by Nejat et al in 2011 reported that blood types A and AB are more associated with low ovarian reserve [57]. However, such results were not repeated in other subsequent studies, including a metaanalysis on the subject [58][59][60].…”
Section: Abo Blood Typementioning
confidence: 99%
“…Moreover, a report by WebMD Health News [23], proposed that type O blood is associated with infertility. According to some studies, women with antigen B are more likely to develop DOR [24], and subsequent studies found that ABO blood group had no effect on ovarian reserve or ovarian response [25][26][27][28][29][30]. Lin et al showed that Chinese women with blood type O had less diminished ovarian reserve than women with blood type B and AB, which were more frequently associated with diminished ovarian reserve, whereas blood type A was not associated with ovarian reserve [24].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also reported the relationship between the ABO blood group and ovarian reserve, and showed that blood group O is more likely to have diminished ovarian reserve (DOR) [ 9 , 10 ]. Whereas some studies found that women with antigen B are more likely to have DOR [ 11 ], and subsequent studies found that ABO blood group was not related to ovarian reserve or ovarian response [ 12 17 ]. Research reports on the relationship between ABO blood group and ovarian hyperstimulation syndrome (OHSS) were also inconsistent [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%